32 SOCIOECONOMIC STATUS AND OUTCOME FOLLOWING CARDIAC ARREST. Issue 1 (1st January 2007) - Zhang, W.; Rea, T. D.; Eisenberg, M. S.
Abstract : Background: Out-of-hospital cardiac arrest due to ventricular fibrillation (OHCA) is a leading cause of mortality, resulting in hundreds of thousands of deaths per year in the United States. Despite ongoing resuscitation efforts, survival has remained poor, less than 20% in most communities. Efforts to improve survival require a better understanding of characteristics that influence survival. Factors related to OHCA circumstances or care are well-established determinants of outcome. More recently, surrogate measures of socioeconomic status (SES) as defined by census tract or property values have been related to survival following OHCA. Health disparities related to SES identify a potential opportunity to improve outcome if the disparity can be characterized. To improve our understanding of how SES influences survival following OHCA, we investigated the relationship between traditional measures of SES and well-established predictors of survival following OHCA. We hypothesized that traditional measures of SES would be associated with established circumstance and care predictors of survival. Study Design and Methods: This investigation is a retrospective cohort study of OHCA treated by emergency medical services (EMS) between January 1, 1999, and December 31, 2004, in King County, WA. Information about each case is abstracted from EMS reports, hospital records, and/or death certificates using a standard data collection form. Measures of SES included race education, marital status, and occupation. We compared the prevalence of these traditional SES measures with established predictors of OHCA (age, citizen CPR, witness status, EMS response interval). Results: A total of 1, 198 persons suffered OHCA due to heart disease during the study period. Of these, 866 (72.2%) had complete information. In some instances, traditional measures of SES were associated with predictors of survival. For example, citizen CPR was more common among Caucasians (58%) compared with other races (52%). In other instances, traditional SES measures were not associated with predictors of survival. For example, race was not associated with witness status. Conclusion: This work begins to delineate the relationship between traditional measures of SES and established predictors of survival following OHCA. Ongoing effort is addressing missing data and incorporating multivariable modeling to best assess the contribution of traditional SES measures.